Performance assessment and major trends in open government data research based on Web of Science data. (1st July 2019) - Lv, Hong; Ma, Haiqun
Abstract : Purpose: The purpose of this paper is to evaluate the global progress and explore research areas and development trends of open government data (OGD) field from the Web of Science (WOS) database by applying the bibliometric visualization approach. Design/methodology/approach: This paper conducted a bibliometric mapping study on OGD scientific research publications based on WOS from six aspects. Findings: There are six research perspectives on OGD research. European countries and developed countries pay more attention to OGD movement. The 20 most cited and highly influential research documents were identified. What's more, the analysis of journals level highlights the interdisciplinary and cross-disciplinary characteristics of OGD research. Current six research topics for OGD research that have been formed and two major emerging research priorities in OGD research fields were identified. Research limitations/implications: The limitation is that data retrieval result which decided to include only 180 publications in the WOS-indexed publications produced a bias against research publications published in non-WOS publication sources. A fuller research trend would be obtained with the more extensively used electronic databases. Practical implications: By dint of bibliometric analysis, this paper may be able to quantify research patterns on OGD, to analyze what has been done in this field and to identify the main research hotspots. Therefore, it can aid academic researchers and practicing professionals in contributing to the field more effectively and advancing scientific progress in the field of OGD research. Social implications: The results can also promote the study on OGD movement in academia, government and industry and also enrich the theory of OGD and provide some new perspectives for research on OGD. Originality/value: This is the first study to quantify and evaluate global research patterns and development trends in OGD research based on WOS database, which provides a quantitative perspective on OGD studies that may assist in advancing the development of the field.